2014
DOI: 10.1159/000357075
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Breath Washout Is Feasible in the Clinical Setting and Detects Abnormal Lung Function in Infants and Young Children with Cystic Fibrosis

Abstract: Background: Cystic fibrosis (CF) lung disease starts in the first months of life often before the onset of clinical symptoms. Multiple breath washout (MBW) detects abnormal lung function in infants and young children in the laboratory setting. Objective: The aim of this study was to determine the feasibility of MBW in 0- to 4-year-old children with CF and non-CF controls in the clinical setting. Methods: Fourteen children with CF (mean age 1.3 ± 1.0 years) and 26 age-matched non-CF controls were sedated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 33 publications
5
45
1
3
Order By: Relevance
“…These results strongly suggest that early rescue of CFTR function may be essential to prevent and/or delay irreversible lung damage in CF. As sensitive noninvasive outcome measures for assessment of abnormal lung structure and function in infants and young children, such as computed tomography, magnetic resonance imaging and multiple breath washout, are becoming available [28,38,[83][84][85][86], the ivacaftor clinical trial programme should be extended to studies in CF infants as soon as possible to exploit the narrow window of opportunity that has been created by widespread implementation of newborn screening and determine to what extent early therapy can delay or even prevent irreversible lung damage in CF.…”
Section: Can Cftr Modulator Therapy Prevent Cf Lung Disease?mentioning
confidence: 99%
“…These results strongly suggest that early rescue of CFTR function may be essential to prevent and/or delay irreversible lung damage in CF. As sensitive noninvasive outcome measures for assessment of abnormal lung structure and function in infants and young children, such as computed tomography, magnetic resonance imaging and multiple breath washout, are becoming available [28,38,[83][84][85][86], the ivacaftor clinical trial programme should be extended to studies in CF infants as soon as possible to exploit the narrow window of opportunity that has been created by widespread implementation of newborn screening and determine to what extent early therapy can delay or even prevent irreversible lung damage in CF.…”
Section: Can Cftr Modulator Therapy Prevent Cf Lung Disease?mentioning
confidence: 99%
“…In addition, it is feasible to perform the test in all age groups [7,[17][18][19], and there are now commercial devices available to facilitate testing in the clinical setting. Currently, less is known about the ability of LCI to detect treatment response in patients with moderate-to-severe lung disease; a population that is more likely to require hospitalisation for pulmonary exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, STAHL et al [48] found a significantly higher LCI in CF children with a mean age of 1.3¡1.0 years compared with controls, implicating the importance of screening and early treatment to keep the lungs normal.…”
Section: Cystic Fibrosismentioning
confidence: 84%